Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2021)
A dataset containing 39529649 species occurrences available in GBIF matching the query: { "Continent" : [ "is North America" ] } The dataset includes 39529649 records from 720 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0335868-200613084148143/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences